2017
DOI: 10.3389/fnins.2017.00116
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Regulates the Growth of Neuroblastoma Cells in vitro and in vivo

Abstract: Background: Neuroblastoma is the most common extracranial tumors in children. At present about the true etiology of neuroblastoma is unclear and many studies have tried to find effective treatments for these primary malignant tumors. Although it has been illustrated that androgen receptor (AR) was expressed in neuroblastoma cells in some former reports, the biological role of androgen receptor in the development of neuroblastoma is not fully understood.Methods: Androgen (R1881) and the antagonists of androgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Therefore, we have investigated the influence of both hormones on the expression of the SHANK genes, which are strongly linked to ASD pathology (Leblond et al, 2014 ). We could show in the SH-SY5Y neuroblastoma cell line, a widely used neuronal cell model to investigate hormonal influences of androgens and estrogens (Sarachana et al, 2011 ; Grassi et al, 2013 ; Nakaso et al, 2014 ; Sun et al, 2017 ), that the effect of DHT and 17β-estradiol on the expression of all three Shanks could be effectively blocked by androgen and estrogen receptor antagonists. SHANK gene expression was shown to be regulated by DHT, directly modulated by AR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have investigated the influence of both hormones on the expression of the SHANK genes, which are strongly linked to ASD pathology (Leblond et al, 2014 ). We could show in the SH-SY5Y neuroblastoma cell line, a widely used neuronal cell model to investigate hormonal influences of androgens and estrogens (Sarachana et al, 2011 ; Grassi et al, 2013 ; Nakaso et al, 2014 ; Sun et al, 2017 ), that the effect of DHT and 17β-estradiol on the expression of all three Shanks could be effectively blocked by androgen and estrogen receptor antagonists. SHANK gene expression was shown to be regulated by DHT, directly modulated by AR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study suggested that NB cells may produce androgens for the growth of themselves ( 6 ). Here the production of hormones of cultured SH-SY5Y cells in comparison with HepG2 cells were determined with LC-MS/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we found that the androgen receptor (AR) agonist, R1881, promoted the growth of NB in vitro and in vivo and the AR antagonists, MDV3100 and ARN509, significantly decreased the proliferation, migration, invasion, and sphere formation of NB cells cultured in hormone-free medium ( 6 ). The findings suggested that NB cells were able to produce androgens for the growth of themselves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, being male sex hormones, androgens are responsible for the development of adult sexual functions and distinguishing of the male reproductive system. Moreover, androgens are required for various anabolic functions in several tissues/organs such as the muscle, bone (Chang et al, ; Takayama ) and the brain (Chang et al, ; Fargo, Galbiati, Foecking, Poletti, Jones Kathryn, , Gaignard et al, ). Multiple clinical cohorts reported that age‐related decline of serum androgen specifically promoted the development of Alzheimer's disease (AD; George, Petit, Gouras, Brundin, & Olsson, ; Rosario et al, ; César Vieira Juliany et al, ; Wahjoepramono et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that PSF/SFPQ, an RNA‐binding protein, is implicated in AR signaling because of its ability to splice RNA and consequently regulate epigenetic conditions (Takayama et al, ). In the present study, we explored the regulatory mechanisms of APP expression associated with AR and PSF using SH‐SY5Y cells derived from the human neurons (Butler, Leigh, & Gallo, ; Matsumoto et al, ), which express endogenous AR and exhibit androgen‐dependent cell growth (Sun et al, ). Moreover, as in previous reports (Ke et al, ; Liang et al, ; Moosecker et al, ), the expression and function of several key factors such as APP and Tau proteins have been analyzed in SH‐SY5Y cells.…”
Section: Introductionmentioning
confidence: 99%